The Emergence of Interior Architecture - Darbandi, Maryam; Imani, Nadieh; Rahimzadeh, Mohammadreza (UI Scholars Hub, 2023)
Less than a century has passed since the creation or at least the use of the term interior architecture. Although interior architecture had existed before and was considered an inseparable part of architectural work, some developments and changes became the basis for the formation of interior architecture and, as a result, its appearance independently of architecture. The main impact of these developments in the independence of interior architecture can be traced to the 19th and 20th centuries when the field of two specialisations of the same family, interior decoration and interior design emerged. This article aims to take a step towards understanding what interior architecture is by understanding the origin or emergence of this speciality. Therefore, in this research, firstly, the background of the emergence of interior decoration and interior design is discussed, then why and how interior architecture appeared is investigated and analysed. The methodology of this research is interpretive-historical and the findings are expressed using graphical methods in the form of flow charts, timelines, and diagrams. In the conclusion of this research, a conceptual model is presented to explain the impact of the emergence of these three specialities on each other.